Depression and Anxiety Problems Among Adolescents at Puskemas Grogol Petamburan - Lestari, Sri; Theresia, Tiarma Talenta; Septifionna, Haura Agni; Nathania, Cindy; Wijaya, Johanna Augusta; Gabriela, Maria; Gustiawan, Muhammad Rakha; Urrohman, Auliya; JK, Febry Anggreani (PROMOTOR, 2025)
Background: Depression is a mental disorder characterized by sadness, loss of interest or pleasure, feelings of guilt, low self-esteem, difficulty sleeping, changes in appetite (either decreased or increased), fatigue, and lack of concentration. Anxiety, on the other hand, refers to tension, insecurity, and worry that arise due to unpleasant circumstances. According to the World Health Organization (WHO), mental health issues are more likely to occur in adolescents, a transitional phase from childhood to adulthood. The prevalence of depression and anxiety among adolescents in Indonesia is 20.8% and 34.6%, respectively. The Adolescent Care Health Service (PKPR) is a government program aimed at preventing health issues among individuals aged 10–19 years at community health centers (Puskesmas). Objective: This study aims to examine the implementation of the Adolescent Care Health Service (PKPR) in addressing cases of depression and anxiety at the Grogol Petamburan Public Health Center. Methods: The study employed a descriptive observational design with a cross-sectional approach. Secondary data were collected through interviews with PKPR staff at the Grogol Petamburan Public Health Center using the SDQ-25 questionnaire and analyzed using descriptive analysis. Results: Counseling data revealed that among 20 cases of depression handled, 14 showed improvement, while 6 were referred to the hospital. Regarding anxiety cases, 15 cases were addressed, of which 11 showed improvement, and 4 were referred to the hospital. Conclusion: The high prevalence of depression and anxiety among adolescents is attributed to the lack of public knowledge in Grogol Petamburan about prevention, symptoms, and management of these conditions.